The Empowerment of Vegetable Farmers Group through the Implementation of Healthy Agriculture at Vegetable Farmers Center in Bokor Village, Tumpang Subdistrict, Malang Regency East Java Province - Nurul Aini; Wiwin Sumiya Dwi Yamika; Kartika Yurlisa; Fery Abdul Cholid; Faizatul Amalia; Joko Prasetyo (Universitas Islam Kadiri, 2019)
The empowerment activity was motivated by excessive use of inorganic fertilizers, chemical pesticides and herbicides in the process of vegetable cultivation and other agricultural commodities in the vegetable center of Bokor Village. The high cost of labor for weed control causes farmers to overuse herbicides. The practice of vegetable cultivation with high chemical inputs has an impact on agricultural land degradation, high costs of productions and chemical residues in vegetable production. On the long period, chemical residues can endanger consumer’s health. The objectives of this service are: 1). Increasing awareness of farmers to cultivate vegetables that are safe for consumption with the principles of healthy farming; 2). Reducing damage to agricultural ecosystems due to unhealthy agricultural practices. Mentoring activities are carried out during May-September 2018 (5 months), with a target of 20 participants. The methods of activities that carried out was a survey and discussion of the implementation of healthy farming with the Bokor Village farmer group; comparative study on the Brenjonk Organic Community, Trawas, Mojokerto; then followed by mentoring vegetable cultivation using biological agents in the study plot.From the results of the mentoring activity, it can be concluded: 1. It has provided knowledge and skills to farmers to implement healthy farming, 2. It has been running quite effectively by looking at the results of evaluations that are in line with the achievement targets.